Inhibition of inactivation of single sodium channels by a site-directed antibody. - Vassilev, P (1989)
The effects of site-directed antibodies on single sodium channel currents in excised membrane patches from rat brain neurons have been examined. Of six antibodies directed against different intracellular domains of the sodium channel alpha subunit, only an antibody directed against a highly conserved intracellular segment between homologous transmembrane domains III and IV induced late single channel openings and prolonged single channel open times during depolarizing test pulses, resulting in nearly complete inhibition of sodium channel inactivation. The antibody effect was not observed if the membrane patches were depolarized to inactivate sodium channels before exposure to the antibody, indicating that the intracellular sequence recognized by the antibody is rendered inaccessible by inactivation. The results show that a conformational change involving the intracellular segment between domains III and IV of the alpha subunit of the sodium channel molecule is required for fast sodium channel inactivation and suggest that this segment may be the fast inactivation gate of the sodium channel.